Strategi Komunikasi Divisi P2M Badan Narkotika Nasional Kabupaten Nganjuk Dalam Membangun Ketahanan Keluarga Anti Narkoba - Bayu Asmoro; Syifa Syarifah Alamiah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The P2M Division is a division of the National Narcotics Agency that is tasked with prevention and community empowerment, which functions to expand information related to the dangers of using drugs, preventing the use of narcotics and how to deal with them if they have fallen into narcotics. The type of research used is descriptive qualitative by applying data collection methods through in-depth interviews, observation, and documentation. Technical data analysis includes data collection, presentation, data reduction, and drawing conclusions. The purpose of this study is to find out the communication strategy of the prevention and community empowerment division of the National Narcotics Agency of Nganjuk Regency in building anti-drug family resilience. The results obtained from this study are that the implementation of the communication strategy of the P2M division of the BNN in Nganjuk Regency to conduct counseling in building anti-drug family resilience is to apply the 5-step communication strategy model proposed by Hafied Cangara.